Do Managerial Resources for Procurement 4.0 Influence the Circular Economy Openness of Managers? - Ovidiu-Iulian BUNEA; Razvan-Andrei CORBOS (Communications of International Proceedings, 2022)
The aim of this paper is to identify potential influences of managerial resources for the implementation of Procurement 4.0 on the level of openness of managers regarding the circular economy, respectively, on the adoption of the principles it implies. To achieve this goal, we had a quantitative approach. Thus, we applied a questionnaire to selected managers of Romanian companies and obtained a number of 85 valid responses. We use Pearson's correlation to test the influences. The results indicated that there are potential positive influences of managerial resources for Procurement 4.0 on the circular economy openness of managers. As a number of previous studies have shown that the technologies implemented in procurement positively influence the organization's level of readiness for the circular economy, we believe that the results presented in this paper provide insights into the importance of organizations' managerial resources regarding Procurement 4.0. such as the adoption of the principles of the circular economy and is a starting point for further investigation.
Keywords: Procurement 4.0; Circular Economy; Sustainability; Management.